2012
DOI: 10.1176/appi.neuropsych.11020048
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive-Spectrum Symptoms in Patients With Focal Dystonia, Hemifacial Spasm, and Healthy Subjects

Abstract: This study is aimed at investigating obsessive-compulsive disorder (OCD) in three groups of patients matched for age and gender; namely, focal dystonia (FD), hemifacial spasm (HFS), and healthy-control subjects (HC). All subjects were investigated with the Structured Clinical Interview for DSM-I, the Hospital Anxiety and Depression Scale, the Symptom Checklist-90, the Yale-Brown Obsessive-Compulsive Scale, and the Structured Clinical Interview for Obsessive-Compulsive Spectrum Self-Report, Lifetime Version (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…In this study, depressive disorders, and not OCD or anxiety, were the specific abnormalities identified; further, these were restricted to patients with cervical dystonia and blepharospasm, and were not observed in those with spasmodic dysphonia or brachial dystonia. Other studies using healthy and disease control groups, however, do find an increased risk of OCD, although depressive symptoms and anxiety were common …”
Section: Can Dystonia Be Primary If It Is Not “Pure”?mentioning
confidence: 78%
See 1 more Smart Citation
“…In this study, depressive disorders, and not OCD or anxiety, were the specific abnormalities identified; further, these were restricted to patients with cervical dystonia and blepharospasm, and were not observed in those with spasmodic dysphonia or brachial dystonia. Other studies using healthy and disease control groups, however, do find an increased risk of OCD, although depressive symptoms and anxiety were common …”
Section: Can Dystonia Be Primary If It Is Not “Pure”?mentioning
confidence: 78%
“…Other studies using healthy and disease control groups, however, do find an increased risk of OCD, although depressive symptoms and anxiety were common. [51][52][53] Sensory abnormalities have also been a subject of investigation in primary adult-onset focal dystonia patients. Clinically evident sensory abnormalities are not associated with the focal dystonias, and when present trigger consideration of other diagnoses; however, the prominent presence of pain (especially in cervical dystonia) and efficacy of sensory tricks or "geste antgoniste" have long suggested sensory processing impairments.…”
Section: Non-motor Abnormalities In Adult and Focal Subtypes Of Primamentioning
confidence: 99%
“…In the study by Munhoz et al (2005) 67% of patients with blepharospasm and 70% of those with HFS met the DSM-IV criteria for OCD, and, although this difference was not significant, the severity of OCD was greater in patients with blepharospasm. Similarly, Mula et al (2012) found equivalent rates of OCD in 26% of patients with focal dystonia (8 blepharospasm and 11 CD) and 28% of HFS, which were higher than in healthy controls; although, the rates of depression or anxiety did not differ from healthy controls. Furthermore, in their sample of 15 patients with CD, 15 with blepharospasm and 15 with writer's cramp, Bugalho et al (2008) reported that only three fulfilled DSM-IV criteria for clinical OCD, but significantly more patients scored above the cut-off score on the YBOCS than healthy controls.…”
Section: Blepharospasmmentioning
confidence: 82%
“…It remains unclear why obsessive-compulsive symptoms are not universally present in primary focal dystonia, but reported results might suggest a common neurobiological basis related to cortical-basal dysfunction [46]. On the other hand, a study, although small-sampled, found OCD to be increased both in focal dystonia and in HFS, compared to healthy controls, but with significant between groups thematic content, and usually with mild severity [58]. No significant differences in obsessive-compulsive symptoms emerged in a study comparing DYT1 carriers to a control population [57].…”
Section: Epidemiological and Etiological Basismentioning
confidence: 87%